Peran Dinas Pariwisata Dan Kebudayaan Dalam Mengoptimalkan Potensi Pariwisata Berbasis Ekonomi Kreatif di Pantai Pengandaran - Sulasih, Sulasih; Lutfi, Nur Aini Dian (Jaanur Elbarik Indonesia, 2026)
The Department of Tourism and Culture (Disparbud), according to Regional Regulation Number 6 of 2018 on the Formation and Structure of Regional Apparatus of Pangandaran Regency, is a regional apparatus responsible for managing government affairs in the fields of tourism and culture. It is led by the Head of the Department, who reports directly to the Regent through the Regional Secretary. The Head of the Department oversees five divisions in carrying out its duties: Secretary, Tourism Destination Division, Tourism Industry and Creative Economy Division, Tourism Analysis and Marketing Division, and Cultural Division. The research uses a descriptive qualitative method with a case study approach. Data were collected through interviews, observations, and documentation, with informants consisting of the Head of the Tourism Department, local creative economy players, and tourists. Data analysis was carried out using data reduction, data presentation, and conclusion drawing techniques. This research focuses on the programs implemented by the department and the contribution of the creative economy industry to the development of tourism in Pangandaran. The results show that the Department of Tourism and Culture of Pangandaran Regency plays a significant role in enhancing the quality and competitiveness of tourism through collaboration with creative economy actors. However, challenges remain, such as the lack of technological infrastructure and low public awareness of the importance of the creative economy in supporting sustainable tourism.